DNA RESEARCH CONFIRMS THAT MA JORITY OF MALAYS ORIGINATED FROM THE SUNDA SHELF - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 6 April 2015 DNA research has shown that the majority of Malay ethnic groups has deep ancestries from the region of the remaining Sundaland, which is the presentday Southeast Asia, after it has undergone several seawater rises due to postglacial floodings since 25,00021,000 years ago.